A Concrete Situation For Learning Decimals - Puri Pramudiani; Zulkardi Zulkardi; Yusuf Hartono; Barbara van Amerom (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2011)
Learning about decimals is an important part in mathematics. However at the same time, decimals are known as the abstract numbers for students. Mostly in Indonesia, decimal is taught only as another notation for fractions or percentages. There are no meaningful references for them such as the use of concrete situations. This study aimed at investigating one situation that enables students to learn about decimals in a meaningful way, i.e. measurement activities. Design research was chosen to reach the research goal. Realistic Mathematics Education (RME) underlies the design of context and activities. Our findings are that the students could discover decimals and get meaningful situation from it. Measurement activities can promote the students’ notion of decimals which, then, provoke the students’ thinking into the idea of using number line as a model for placing the magnitude of decimals. Based on these findings, it is recommended that RME be implemented as an approach of teaching and learning decimals.Keywords: decimals, Realistic Mathematics Education (RME), number line, design research. DOI: http://dx.doi.org/10.22342/jme.2.2.750.215-230